ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA MATERI OPERASI BILANGAN PECAHAN DI KELAS IV SDN 101893 BANGUN REJO - Indah Aminah Nasution; Hasanah Hasanah (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the learning process of students and their difficulties as well as the factors that cause students' difficulties in learning mathematics on the material of fractional operations. This research was conducted at SD N 101893 Bangun Rejo. The method used in this study is a qualitative method by analyzing the data in the form of descriptive analysis. The instruments and data collection techniques used in this study were observation, interviews and documentation. From the results of the study, it is known that the mathematics learning process for fourth grade students in the material of fractional operations is not going well. During the learning process, students do not have interest and motivation in participating in the learning process. The difficulties experienced by students in participating in the mathematics learning process for fractional number operations are about multiplication and division of fractions, and it is difficult to distinguish between the numerator and denominator. Meanwhile, the factors that cause learning difficulties for fourth grade students come from internal factors and external factors. Internal factors, namely students' negative perspectives on mathematics lessons that are considered difficult and also there is no motivation in students to participate in the learning process. Meanwhile, from external factors, namely the community environment, such as student activities playing outside of school and also the use of mass media, such as cellphones and also games that are increasingly accessible, have a negative impact on students